ISOLATION AND SCREENING OF ANTIMICROBIAL PEPTIDES FROM KANTHARI MULAKU (CAPSICUM FRUTESCENS) - SONA S DEV,; AKHIL VENU, (International Journal of Pharma and Bio Sciences, 2016)
Kanthari mulaku (Capsicum frutescens), as it is known in Kerala, India is one of the most commonly used pepper species in cooking as well as folk medicine. The work was carried out to isolate, purify and test the efficacy of the antimicrobial peptides (AMPs) from this species.The purified peptide fraction when tested against E coli, Staphylococus aureus and Klebsiella pneumonia by disk diffusion method showed inhibition zones of 3 to 12 mm range at 250 mg/ml concentration. The fungus Alternaria and Colletotrichum showed 100% inhibition of growth and Fusarium showed 66% inhibition of growth at 5 mg/ml concentration of fruit extract. The leaf extract however showed 75%, 12.5 % and 17.5% growth inhibition of Alternaria, Colletotrichum and Fusarium at 5 mg/ml concentration. On the basis of these findings, it can be concluded that the purified antimicrobial peptide from C frutescens could play strong roles in agriculture as a natural pesticide against various phytopathogens.